Atrial fibrillation and chronic kidney disease: main clinical characteristics of patients in selected subjects of the Russian Federation - M. A. Druzhilov; T. Yu. Kuznetsova; O. Yu. Druzhilova; U. D. Arustamova; D. V. Gavrilov; A. V. Gusev (Кардиоваскулярная терапия и профилактика)
Aim. To compare clinical characteristics of patients with atrial fibrillation (AF) depending on renal filtration function based on a retrospective analysis of data in individual subjects of the Russian Federation (RF).Material and methods. The information was taken from the Webiomed predictive analytics platform, including 80775 patients with AF (men, 42,5%, mean age, 70,0±14,3 years) who underwent outpatient and/or inpatient treatment in medical organizations in 6 Russian subjects in 2016-2019 with data on blood creatinine levels. For comparative analysis, the ranges of estimated glomerular filtration rate (eGFR) were selected: ≥60 ml/min/1,73 m2, 30–59 ml/min/1,73 m2, and <30 ml/min/1,73 m2.Results. The analysis showed that 45128 (55,9%) patients were characterized by eGFR <60 ml/min/1,73 m2, of which in 35212 (78%) patients eGFR was in the range of 30-59 ml/min/1,73 m2, in 9916 (22%) — <30 ml/min/1,73 m2. Patients with eGFR <60 ml/min/1,73 m2 compared with those with eGFR ≥60 ml/min/1,73 m2 were older (75,4±10,9 vs 63,0±15,2 years, p<0,001), had higher incidence of ischemic stroke (IS) (10,9 vs 6,5%, p<0,001), myocardial infarction (MI) (11,5 vs 7,7%, p<0,001) and intracranial hemorrhage (ICH) (1,0 vs 0,7%, p<0,01), as well as higher rate of anticoagulant therapy (ACT) (47,0 vs 33,2%, p<0,001). Men and women with eGFR of 30-59 and <30 ml/min/1,73 m2 in the age ranges ≤64 years and 65-74 years had a higher incidence of IS and MI compared with patients with eGFR ≥60 ml/min/173 m2. The frequency of ICH on warfarin compared with direct oral anticoagulants was significantly higher in the subgroup with eGFR of 30-59 ml/min/1,73 m2 (1,1 vs 0,7%, p<0,01).Conclusion. Patients with AF and eGFR <60 ml/min/1,73 m2 are characterized by greater comorbidity, a higher incidence of IS, MI and ICH compared with patients with AF and eGFR ≥60 ml/min/1,73 m2, while ACT prescription rate as of 2016-2019 in some Russian subjects was unsatisfactory. This emphasizes the need to optimize risk stratification, ACT and algorithms for the prevention of atherothrombotic events, as well as the development of nephroprotective strategies to reduce the rate of progression of renal dysfunction in this cohort of patients.